Storms, floods, landslides and elections in India's growing metropolises: Hotbeds for political protest? - Viktoria Jansesberger (University of Konstanz, Cluster of Excellence "The Politics of Inequality", 2024)
Do sudden weather disasters in cities of the Global South increase the likelihood of anti-government protests? In cities of the Global South, floods, storms, and landslides strain already fragile infrastructure, often leading to destruction and hardship. While urban residents occasionally protest in response to such dire conditions, they often do not. Thus, this paper addresses the question of when this is more likely to occur. I argue that sudden destructive weather events spark anti-government protests if they coincide with upcoming elections as organizing protests can serve as a strategy by political actors to gain attention and mobilize voters. Given the increased public attention, citizens might furthermore consider it a good time to voice their dissatisfaction. I test this hypothesis using novel self-compiled protest data on 19 Indian metropolises (2000-2019). Quantitative regression analyses on samples pre-processed with Coarsened Exact Matching and insights from illustrative examples yield robust support for the argument.
urn:nbn:de:bsz:352-2-mgyzx9t2nc5z3
Keywords: 320; Katastrophe; Protestbewegung; Wahl; Ballungsraum; Indien